2001
DOI: 10.1093/humrep/16.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked hyaluronate hydrogel prevents adhesion formation and reformation in mouse uterine horn model

Abstract: The aim of this study was to evaluate the efficacy of cross-linked hyaluronate hydrogel (HA gel) as an adjuvant for postoperative adhesion prevention, in a mouse uterine horn model. In experiment 1 uterine horns were abrased with iodine. HA gel was applied to the injured surface before closure in the treatment group. In experiment 2, after injuring the uterine horns, three stitches were placed at equal distances around the uterine horns to appose the injured medial surfaces of the two horns during healing. HA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…However, loss of specific functional groups in tissue interaction minimizes tissue adhesiveness after cross-linking procedure [233]. Crosslinked HA hydrogel is reported to reduce post-operative adhesion prevention in a mouse uterine horn model [234], whereas a recent human study found the gel to reduce intrauterine adhesion formation [235]. It has been suggested that semi-interpenetrating polymer networks of certain natural polymer combinations can be a solution that compensates for the shared problem of natural polymers [236].…”
Section: Barriersmentioning
confidence: 99%
“…However, loss of specific functional groups in tissue interaction minimizes tissue adhesiveness after cross-linking procedure [233]. Crosslinked HA hydrogel is reported to reduce post-operative adhesion prevention in a mouse uterine horn model [234], whereas a recent human study found the gel to reduce intrauterine adhesion formation [235]. It has been suggested that semi-interpenetrating polymer networks of certain natural polymer combinations can be a solution that compensates for the shared problem of natural polymers [236].…”
Section: Barriersmentioning
confidence: 99%
“…Hydrogels were used for reconstruction of the retina [523], ligament [524], fatty tissue [465], kidneys [525], muscles [526], blood vessels [527,528], and also heart, neural cells, invertebral discs, bones and gristle [459]. Hydrogels were used to prevent adhesions [529,530,531], to promote cellular adhesion [490,532,533]. So-called strong hydrogels were developed to improve mechanical properties [534].…”
Section: Selection Of Technologies Of Implantable Devices In Regeneramentioning
confidence: 99%
“…In several groups, adhesions were developed by first causing bleeding followed by suturing of the uterine horn to the peritoneal wall [26,27]. Indeed, one group reported that adhesion formation was guaranteed in mice only if hemorrhage was combined with apposition of the injured surfaces with stitches [28].…”
Section: Mouse Model For Postoperative Adhesion Formationmentioning
confidence: 99%